2019
DOI: 10.1108/bl-12-2018-0051
|View full text |Cite
|
Sign up to set email alerts
|

Advances in intellectual capital performance measurement: a state-of-the-art review

Abstract: Purpose The purpose of this paper is to present a review on the latest developments, approaches and methods in intellectual capital (IC) performance measurement. Design/methodology/approach A total of 53 research papers from high-ranking journals concerning the advances in IC performance measurement were thoroughly reviewed and classified to identify the advanced approaches and methods that have been used to evaluate IC performance. Findings It is clear that the current application of advanced or intellige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 67 publications
0
7
0
1
Order By: Relevance
“…In this sense, the research contribution is threefold. First, the contemporary managerial, economic, political and social relevance of the theme is highlighted by Li et al (2021), Xu and Liu (2020); Lee and Wong (2019), Nadeem et al (2019); and Pedro et al (2018), who noted the vital importance of measuring IC as a means of promoting the competitiveness, innovation, sustainability, wealth and performance of organizations. A recent study by Ocean Tomo (2021), for example, has confirmed that intangible assets accounted for 17% of the market value of the S&P500 in 1975, rising to 68% in 1995, 84% in 2015 and reaching more than 90% in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the research contribution is threefold. First, the contemporary managerial, economic, political and social relevance of the theme is highlighted by Li et al (2021), Xu and Liu (2020); Lee and Wong (2019), Nadeem et al (2019); and Pedro et al (2018), who noted the vital importance of measuring IC as a means of promoting the competitiveness, innovation, sustainability, wealth and performance of organizations. A recent study by Ocean Tomo (2021), for example, has confirmed that intangible assets accounted for 17% of the market value of the S&P500 in 1975, rising to 68% in 1995, 84% in 2015 and reaching more than 90% in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Along the same lines, Edvinsson and Malone (1997) stated that IC is the ownership of knowledge, expertise, experience, technology, and customer relationships, which brings about competitiveness. Numerous studies (e.g., Vishnu & Gupta, 2014;Jelínková & Jiřincová, 2015;Smriti & Das, 2018;Cagáňová et al, 2019;Cheikh & Noubbigh, 2019;Lee & Wong, 2019;Sardo & Serrasqueiro, 2019;Xu & Li, 2019;Yao et al, 2019;Costa et al, 2020;Masoomzadeh et al, 2020;Nigam et al, 2021) have provided evidence that IC can be categorized into human capital (HC), structural capital (SC), and relational capital (RC). Specifically, HC can be considered as an essential factor of firm value creation (Smriti & Das, 2018), and is widely accepted as the amalgamation of skills, competencies, capabilities, and experiences of employees (Morris, 2015;Jelínková & Jiřincová, 2015).…”
Section: Ic Definition and Measurementmentioning
confidence: 99%
“…Also, Kianto et al (2014) defined overall IC as the sum of all of the intangible and knowledge-related resources that an organization is able to use in its production processes in the attempt to create value. While, Lee and Wong (2019) reported that IC embodies the intangible assets and resources of a company, such as knowledge, know-how, professional skills and expertise, employees, databases, intellectual properties, technologies, customers, etc., that can benefit a company and determine its potential to grow in the future when managed and used wisely. Accordingly, IC is not just a static intangible asset, but it is a means to an end (Bontis, 1998).…”
Section: Intellectual Capitalmentioning
confidence: 99%